A parametric analytical model for non-linear dynamics in cable stayed beam. - Gattulli, Vincenzo
The governing equations for dynamic transverse motion of a cable stayed beam are obtained by means of a classical variational formulation. The analytical model permits a parametric investigation of linear and non-linear behaviour in a family of cable stayed beam systems. Analytical eigensolutions of the linearized equations are used to investigate how the mechanical characteristics influence the occurence of global, local and coupled modes. The exact eigenfunctions are assumed to describe the forced harmonic motion in the neighborhood of a selected frequency. The frequency amplitude relationship, obtained by the use of the multiple scale method, permits the description of softening and hardening behaviour in the global, local and coupled classes of motion.
Keywords: Cables; Cable stayed beam; Analytical eigensolutions; Parametric analysis; Sag effects; Multiple scale method; Non-linear oscillations